Influence of high pressure compaction on solubility and intrinsic dissolution of ibuprofen binary mixtures employing standard excipients - Bashar Ibraheem; Karl G. Wagner (Elsevier, 2021)
Enabling formulations often depend on functional excipients. However, the question remains whether excipients regarded as standard establish similar interactions and subsequently improvement of solubility when employed at unusual manufacturing process conditions. In this study, compaction of API under high pressure in the presence of hydrophilic excipients is proposed as a technique to improve the solubility and/or dissolution rate with an acceptable preservation of the supersaturation state. Binary mixtures of ibuprofen (IBU) with hydroxypropyl cellulose, isomalt, mannitol and sorbitol were compacted applying high pressure (500 MPa) with and without a previous co-milling step. Intrinsic dissolution rate (IDR) was selected to characterize and evaluate dissolution performance. The IDR of neat IBU increased from 5 to 88 fold and the aqueous solubility in the range of 3 to 54%. Regarding the polyols isomalt showed the highest impact on solubility and dissolution, without changing the crystallinity of IBU independent of a co-milling step. Even higher impact was achieved in combination with HPC. However, only without a previous co-milling step, ibuprofen remained crystalline, while co-milling induced an amorphous IBU-content of 38%. Based on XRPD and DSC findings, higher IDR and solubility values correlated with crystal modifications as well as IBU/excipient interactions.